Comparison of retention and fracture load of endocrowns made from zirconia and zirconium lithium silicate after aging: an in vitro study - Majid Sahebi; Safoura Ghodsi; Parsia Berahman; Amirhesam Amini; Somayeh Zeighami (BMC, 2022)
Abstract Background This study aimed to compare retention and fracture load in endocrowns made from translucent zirconia and zirconium lithium silicate. Methods Fifty-six intact human maxillary molars after being mounted in acrylic resin, were scanned to acquire biogeneric copies. Specimens underwent standard endodontic treatment and were prepared for endocrown up to 2 mm above the cementoenamel junction. The specimens were randomly divided into two groups of 28, and endocrowns were designed using biogeneric copies and milled from high-translucent zirconia disks (Zr) and zirconium lithium silicate blocks (ZLS). After cementation with dual-cure resin cement, all the specimens underwent thermomechanical aging, and pull-out retention test and compressive test were conducted (14 specimens were used for each test in each group, n = 14), and failure modes in both tests were evaluated. Results Independent samples t-test showed significant difference between the retention of Zr (271.5 N ± 114.31) and ZLS (654.67 N ± 223.17) groups (p value = 0.012). Compressive test results were also significantly different between Zr (7395.07 N ± 1947.42) and ZLS (1618.3 N ± 585) (p = 0.002). Failure mode of retention test was primarily adhesive failure at the cement-restoration interface in Zr group and cement-tooth interface in ZLS group. Failure modes of fracture test for Zr group were 7 non-restorable fractures and one restorable fracture while 6 specimens resisted compressive loads up to 8500 N without fracture. ZLS group showed 7 restorable and 7 non-restorable failures. Conclusions Zr endocrowns showed significantly lower retention and higher fracture strength. Both materials seem to be suitable for fabrication of endocrown in clinical setup.